The application of the Flight Safety Index in the land use planning of the Liszt Ferenc International Airport regarding to the hazardous bird species - Balázs, Gergely; Grónás, Viktor; Heltai, Miklós; Bleier, Norbert (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
The investigation carried out to determine the reliability and the application of the Flight Safety Index (FSI), and Flight Safety Relevance (FSR) (MORGENROTH, 2003) in land use planning for the Liszt Ferenc International Airport (Budapest, Hungary). The FSI values were compared with the long term collision records to test their reliability. The FSI values were calculated according to the local circumstances for each bird species occurring in and around the airport. The bird collision data were collected from the Wildlife Control Diary covering 14 years from 1998 to 2011. We listed the species in FSR3-4-5 categories and compared with the list of species involved in more than 1% of the certain collisions. As a result, 8 species out of total 10 were on both lists: Kestrel Falco tinnunculus, Common Buzzard Buteo buteo, Rook Corvus frugilegus, Common Starling Sturnus vulgaris, Domestic Pigeon Columba livia d., Common Magpie Pica pica, Long-eared Owl Asio otus, Blackheaded Gull Larus ridibundus. The explanation of the two remaining species is simple. House Sparrow Passer domesticus is not on the FSI list because its small body mass reduces flight safety hazard significantly. Carrion Crow Corvus corone is not on the collision list because flocking birds are easier to detect and deter in time and therefore actual collisions happen rarely. That shows that FSI values are fairly reliable, so by purposefully influencing its calculation parameters -like the phenological status, the overflight from the surroundings, the occurrence (density), and habitat preference- by land use planning is a good way to achieve the most beneficial results towards safety.
Keywords: land use planning; wildlife controll; flight safety